Raw data on pollen and spores counts from the sedimentation record/JAM2 sediment trap off SW Java in the Indian Ocean under reverse monsoon conditions - Anastasia Poliakova; Tim Rixen; Tim C Jennerjahn; Hermann Behling (PANGAEA, 2022)
Settling particles collected in a sediment trap 60 km off SW Java in the Indian Ocean at a 2200 m deep site, about 830 m above the sea floor, between December 2001 and November 2002 (intervals of 16 days for 11 months) were analyzed for the abundance and taxa composition of pollen and spores. Several factors control their deposition such as the monsoon-driven reversal of the wind directions and ocean currents as well as flowering periods. Long distance transport plays a particular role during the monsoon seasons. During the NW monsoon (mid-December – beginning of March), maxima of Picea type, Alnus, Pinus and Quercus pollen occur in the trap samples, which corresponds to wind and marine currents coming from the north, probably the Equatorial Counter Current and Southern Java Current, transporting pollen from the southern part of continental Asia and Sumatra to the research area. During the SE monsoon (end of July – mid-November), an increase of pollen originating from southeast Indonesia and Australia was observed. Pollen grains were probably transported by the South Equatorial Current and partly by the Leeuwin Current. Casuarina and, in part, Eucalyptus are most abundant during this period. During the intermonsoon period, assemblages are mainly composed of pollen originating from West Java. Maxima of some pollen taxa, such as Elaeocarpus, Myrica, Dacrycarpus type, Casuarina, Eucalyptus and Podocarpus type probably reflect their flowering periods. The transportation time from the pollen source area to the sediment trap is about 1-2 months. The extrapolated pollen accumulation rate of the marine sediment trap would be about 1670 grains/cm2/yr. The trap collected low concentrations of mangrove pollen, which might be the result of the strong destruction of the mangrove belt in Java during recent decades. High values of Poaceae pollen are probably related to the land use, forest canopy opening and development of the secondary vegetation in West Java. The majority of the pollen and spores collected by the sediment trap reflect the vegetation of SW Java, but long distance transport, in particular by the marine currents during the SE and NE monsoons, needs to be considered when interpreting marine pollen records off SW Java in the eastern Indian Ocean.